The Development Of Learning Video Based On Local Wisdom In The Centre Area And Group Learning In Kindergarten - Sofyan, Hendra (Sekolah Tinggi Agama Islam Al Hidayah, 2022)
The aim of this study was to produce a learning video based on local wisdom in the learning model in early childhood education teacher education in the form of a center model, area model, and group model whose final result was a learning video. The type of this research was development research, namely Research and Development (R&D). The development model used refers to the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The ADDIE model was chosen in this development research based on several reasons, namely, this model is a procedural model, namely a descriptive model, showing clear and careful steps to produce a product. This study resulted, Material Experts stated that the results of this learning video were in the appropriate category, namely the center model obtained a percentage of 87.5%, Area obtained a percentage of 81.25%, and the group obtained a percentage of 82.5%. Meanwhile, media experts also revealed that the results of this learning video were worthy, namely the learning model. The percentage of the center was 86.12%, the area was 88.88%, the group learning model was 94.4% thus all of them was categorized in to the â€œvery goodâ€ criteria.